Pre‐ampullary location and size ≥10 mm are independent predictors for high‐grade superficial non‐ampullary duodenal epithelial tumors. Issue 6 (1st December 2020) - Matsueda, Katsunori; Uedo, Noriya; Kitamura, Masanori; Iwagami, Hiroyoshi; Shichijo, Satoki; Maekawa, Akira; Kanesaka, Takashi; Takeuchi, Yoji; Higashino, Koji; Ishihara, Ryu
Abstract: Background and Aim: The incidence of identified superficial non‐ampullary duodenal epithelial tumors (SNADETs) has been increasing with recent advances in endoscopic diagnosis. Nevertheless, the clinical features of SNADETs with malignant potential remain unclear. The aim of the present study was to clarify the clinical characteristics of high‐grade SNADETs. Methods: A total of 328 SNADETs that had been endoscopically or surgically resected between January 2013 and April 2019 were identified from an endoscopic and pathological database. Clinical characteristics were compared between mucosal low‐grade neoplasm ( n = 154) and mucosal high‐grade neoplasm/submucosal carcinoma (HGN/SMC, n = 174). Results: In univariate analysis, tumor size, pre‐ampullary tumor location, red color, and rough/nodular surface were significantly associated with HGN/SMC. In multivariate analysis (odds ratio [95% confidence interval]), large (≥10 mm) tumor size (odds ratio: 4.5, 95% confidence interval: 2.6–7.7, P < 0.001) and pre‐ampullary tumor location (odds ratio: 2.1, 95% confidence interval: 1.3–3.5, P = 0.004) were independent predictors for HGN/SMC. Analysis of histological phenotypes revealed that the proportion of tumors that were HGN/SMC was much greater for gastric‐type tumors (21/23 lesions, 91%) than for intestinal‐type tumors (150/302 lesions, 50%) ( P < 0.001) and that all gastric‐type tumors were located in the pre‐ampullary portion. Conclusions: Pre‐ampullary location and large tumor size are independent predictors for HGN/SMC SNADETs. Pre‐ampullary tumor location is significantly associated with gastric histological phenotype. These findings may help in decision making for endoscopic treatment, active indication for pre‐ampullary tumor or tumor ≥10 mm, and understanding the pathophysiology of SNADETs.